ALCAM a novel biomarker in patients with type 2 diabetes mellitus complicated with diabetic nephropathy - Sulaj, Alba; Kopf, Stefan; Gröne, Hermann-Josef; Hoffmann, Sigrid; Schwenger, Vedat; Herzig, Stephan; Fleming, Thomas; Nawroth, Peter Paul; Bauer, Rüdiger von (Journal of diabetes and its complications, 2017)
Background & Aim: Activated leukocyte cell adhesion molecule (ALCAM/CD166) functions analogue to the receptor of advanced glycation end products, which has been implicated in the development of diabetic nephropathy (DN). We investigated the expression of ALCAM and its ligand S100B in patients with DN.: Methods: A total of 34 non-diabetic patients, 29 patients with type 2 diabetes and normal albuminuria and 107 patients with type 2 diabetes complicated with DN were assessed for serum concentration of soluble ALCAM (sALCAM) by ELISA. Expression of ALCAM and S100B in kidney histology from patients with DN was determined by immunohistochemistry. Cell expression of ALCAM and S100B was analyzed through confocal immunofluorescence microscopy. Results: Serum concentration of sALCAM was increased in diabetic patients with DN compared to non-diabetic (59.85±14.99ng/ml vs. 126.88±66.45ng/ml, P<0.0001). Moreover sALCAM correlated positively with HbA1c (R=0.31, P<0.0001), as well as with the stages of chronic kidney disease and negatively correlated with eGFR (R=−0.20, P<0.05). In diabetic patients with normal albuminuria sALCAM was increased compared to patients with DN (126.88±66.45ng/ml vs. 197.50±37.17ng/ml, P<0.0001). In diabetic patients, ALCAM expression was significantly upregulated in both the glomeruli and tubules (P<0.001). ALCAM expression in the glomeruli correlated with presence of sclerosis (R=0.25, P<0.001) and localized mainly in the podocytes supporting the hypothesis that membrane bound ALCAM drives diabetic nephropathy and thus explaining sALCAM decrease in diabetic patients with DN. The expression of S100B was increased significantly in the glomeruli of diabetic patients (P<0.001), but not in the tubules. S100B was as well localized in the podocytes. Conclusions: This study identifies for the first time ALCAM as a potential mediator in the late complications of diabetes in the kidney.